Female Portraiture and Patronage in Marie Antoinette's Court - Grant, Sarah, author.
1 online resource (248 pages)
Keywords: This comprehensive book brings to light the portraits, private collections and public patronage of the princesse de Lamballe, a pivotal member of Marie-Antoinette’s inner circle. Drawing extensively on unpublished archival sources, Sarah Grant examines the princess’s many portrait commissions and the rich character of her private collections, which included works by some of the period’s leading artists and artisans. The book sheds new light on the agency, sorority and taste of Marie-Antoinette and her friends, a group of female patrons and model of courtly collecting that would be extinguished by the coming revolution.